Los videos educativos y su incidencia en el aprendizaje de los niños y niñas de educación inicial, nivel ii del cen-tro educativo “Dirigentes del Futuro” de la parroquia Malacatos, del cantón y provincia de Loja, período lec-tivo 2014 – 2015”. Lineamientos alternativos - CHALÁN GUANUCHE, LEYDI VERONICA (2016)
EDUCATIONAL VIDEOS AND IN-incidence LEARNING OF CHILDREN OF EDUCA-TION INITIAL LEVEL II Educational Center "leaders of tomorrow" THE Malacatos, the canton and PROVIN-CIA PARISH Loja LECTIVO PERI-OD 2014- 2015. The main problem was determined: does the videos educati-you influence the learning of children from Early Childhood Education, Level II Educational Center "Leaders of the Future" of Malacatos parish, canton and province of Loja, during the school period 2014-2015. He was raised as General Objective: To determine the incidence of Educa-tional Videos Learning of children in preschool education, Level II Education-al Center "Leaders of the Future" Parish Malacatos Canton and Loja Prov-ince,2014-2015. The methods used for the preparation of this research study were: scientific, inductive, deductive, descriptive statistics that served them effectively to achievetheproposedgoal. The techniques and instruments used in this research were: a survey of the Master, to know the perception teachers on educational videos and an ob-servation guide applied to children. Application of the survey to teachers it is concluded; The teachers if they have a great knowledge about the educa-tional video, answering 100% educational videos that are extremely im-portant for the teaching and learning of children / as.De according to the re-sults of the observation guide: 57 % of children do not have a good learning reaching a rating of unsatisfactory; 22% were able to develop all the activities proposed reaching a rating of very satisfactory, and 21% satisfactory.